(untitled) (Universidad de San Andres Law Review, 2022)
Over the past 15 years, the risks of bribing foreign officials have increased exponentially for multinational companies headquartered in OECD countries, and for those listed on their capital markets. These risks can usually be mitigated if the company or its directors can prove that the conduct occurred despite the existence of prevention and control systems and their effective enforcement. These systems - known as "compliance programs" - are aimed at reducing the supply of bribes and unethical business conduct. This paper describes the international standard governing compliance programs and, on the basis of an empirical exploration of compliance programs in Argentina, discusses the potential for programs in Argentina, discusses the potential that these programs have to reduce - or shift towards companies that do not adopt these standards - the instances of bribe solicitation or acceptance of bribe demands, especially in Argentina.